Coexistência e prevalência de intervenções obstétricas: análise sobre os modelos de assistência ao parto em maternidades públicas e privadas de Belo Horizonte - Karina Cristina Rouwe de Souza (2021)
Introduction The coexistence of obstetric interventions during labor is associated with the model of childbirth care and several factors that may influence this relationship. The aim of this study was to evaluate the coexistence and prevalence profiles of obstetric interventions in public and private maternity hospitals in the city of Belo Horizonte and to investigate the sociodemographic, obstetric and hospital model factors associated with these profiles. Methods: This is an integrative literature review and an observational study with cross sectional design, carried out with data from the research "Nascer em Belo Horizonte: Inquérito sobre o parto e Nascimento", in seven maternity hospitals that serve the public health network and in four maternity hospitals that provide care to the supplementary health network in Belo Horizonte - Minas Gerais, Brazil. Search strategy was carried out in the Pubmed database, and articles that addressed the model of childbirth care were selected. At the end, 20 articles were included. In the cross-sectional study, the interventions analyzed were: offering of diet, freedom to move, use of partogram, non-pharmacological methods for pain relief, enema, trichotomy, lying down position for labor, Kristeller, amniotomy, oxytocin infusion, analgesia and episiotomy. To build the profiles, the variables age, education, skin color, primigravida, financing the place of delivery, number of prenatal visits, gestational age at delivery, presence of an obstetric nurse, paid work, and companion during delivery were considered. The Grade of Membership (GoM) method was used in this study. To verify the magnitude of the association between the generated profiles of coexistence of the performance of obstetric interventions and their possible determinants. Poisson regression models were constructed. Results: The analysis of the selected articles led to the construction of four categories: characterization of the models; avaluation of the models; Model change and challenges for model change. It was also observed the existence of two antagonistic care models in the institutions: the medicalized and the non-medicalized. In the epidemiological study, the results also pointed to the existence of two antagonistic obstetric profiles: profile 1 was constituted by parturients who were offered a diet, had freedom of movement, used a partogram, had non pharmacological methods for pain relief, had given birth in the liying down position, had not been submitted to the were not submitted to Kristeller maneuver, episiotomy or amniotomy, and did not receive oxytocin infusion and use of analgesia. When analyzing the factors that influenced the coexistence of obstetric interventions, it was observed that the financing of the delivery hospital influenced the greater chance of women belonging to profile 2. However, when the hospital had an obstetric nurse present at the delivery scene, there was a reduction in the chance of belonging to profile 2. These results also showed that all women belonging to a given profile tended to receive the same set of interventions, demonstrating that the coexistence of obstetric interventions in the profiles defines two models of childbirth care. Conclusion: Despite advances towards adherence to a model based on scientific evidence, there is still predominance of a reductionist and medicalized model, which refers to professional power. This study contributes to the discussions about obstetric interventions, as well as models of childbirth care, aiming at the implementation of public policies that ensure care based on good labor and birth practices.